Effect of Osmo-Priming with Polyethylene Glycol 6000 (PEG-6000) on Rice Seed (Oryza sativa L.) Germination and Seedling Growth Under Drought Stress - Trisnawaty AR (International Journal of Agriculture System, 2021)
One of the efforts to increase rice production is by extensive farming through the utilization of marginal lands affected by drought. The present study aims to examine the influence of seed priming with PEG 6000 on rice seed germination and growth of rice seedlings in drought conditions and to group the rice varieties tested based on their tolerance to drought, and determine priming formulations for early adaptation of rice seedsthat can be used by farmers and industry.  The research was organized in the form of a Split Plot Design with Randomized Group Design. TheMain Plot is a rice variety, consisting of 10 levels, i.e., Inpari 31, Inpari 33, Inpari 36, Inpari 39, Inpari 40, Inpago 8, Inpago 10, Mekongga,Rindang 1 and Rindang 2. While the Split Plot is a concentration of PEG, which consists of 5 levels, i.e., without soaking as negative controlconcentration 0 g L-1 PEG as positive control, and 50, 100, and 150 g L-1 PEG-6000.  Each of these treatments is repeated three times, so thereare 150 observation units. Results showed that among the 10 varieties tested, there were 2 less tolerant varieties with scores of 5-10 (Inpari 31and Inpari 39), 5 varieties are quite tolerant with a score of 11-16 (Inpari 33, Inpari 36, Inpari 40, Inpagi 10 and Mekongga) and 3 varieties are very tolerant with a score of 17-22 (Rindang 1, Rindang 2 and Inpago 8) with priming concentrations of 100 g L-1 PEG-6000 for 36 hours.